The phenomenon of residual orality in the organization of macrostructure of the book of Revelation - Carvalho, Vitor (2022)
This dissertation analyses how the phenomenon of residual orality has influenced the author of the apocalyptical book of Revelation to organize his textual discourse. I aimed to analyse how the interdependence of residual orality (context of situation) and Christian apocalyptical discourse within the first century (context of culture) contributed to the formation of the macrostructure of the book of Revelation.